Functional Plurality of Language in Contextualised Discourse Eighth Brno Conference on Linguistics Studies in English. Conference Proceedings. Brno, 12-13 September 2019 - Gumbaridze, Zhuzhuna (Masaryk University Press, 2020)
The volume presents eleven articles written by participants of the Eighth Brno Conference on Linguistics Studies in English held in September 2019. The papers (including two plenary speeches delivered by Prof. Julia Hüttner from University of Vienna, and Assoc. Prof. Markéta Malá from Charles University, Prague) offer a range of linguistic topics, covering media discourse, learner discourse (e.g. CLIL), literary genre, language of advertising, and the interdisciplinary approach to language and international relations, to name just a few.